Diagnostic dilemma of chest wall tuberculosis masquerading breast lump and sarcoma/ Nik Aminah Nik Abdul Kadir ... [et al.] - Nik Abdul Kadir, Nik Aminah; Ariffin, Farnaza; Mohamad Ali, Norliana Dalila; Abdul Aziz, Mardiana (Faculty of Medicine, 2023)
Chest wall tuberculosis (TB) is rare and can often masquerade as a tumour. Diagnostic confirmation is made by bacteriological findings of acid-fast bacilli and culture of Mycobacterium tuberculosis or histopathological findings. This is a 37-year-old immunocompetent lady who presented with a 3-month history of gradually increasing right breast lump with suspicious characteristics during clinical examinations. Ultrasound of the breast showed normal breast tissue with a well-defined hypoechoic lesion within the anterior inferior pectoralis muscle. CT scan of the thorax revealed a right anterior chest wall lesion with multiple lung nodules and consolidations. Thus, there was a high suspicion of chest wall tumour and an initial diagnosis of soft tissue sarcoma was made. Biopsy of the lesion showed necrotising granulomatous inflammation but no acid-fast bacilli. A revised diagnosis of chest wall tuberculosis was made. She attended follow-up complaining of shortness of breath and pleuritic chest pain with signs of right pleural effusion. Her symptoms improved after the initiation of anti-TB treatment. This case demonstrated the challenge in making an early diagnosis of chest wall TB and commencement of anti-TB treatment.